2022
DOI: 10.1152/ajpendo.00391.2021
|View full text |Cite
|
Sign up to set email alerts
|

Role of the arterial baroreflex in the sympathetic response to hyperinsulinemia in adult humans

Abstract: Muscle sympathetic nerve activity (MSNA) increases during hyperinsulinemia, primarily attributed to central nervous system effects. Whether peripheral vasodilation induced by insulin further contributes to increased MSNA via arterial baroreflex-mediated mechanisms requires further investigation. Accordingly, we examined baroreflex modulation of the MSNA response to hyperinsulinemia. We hypothesized that rescuing peripheral resistance with co-infusion of the vasoconstrictor phenylephrine would attenuate the MSN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Type 2 diabetes has been shown to significantly modulate muscle metaboreflexinduced peripheral vascular responses by way of enhancing muscle sympathetic nerve activity and the peripheral vasoconstrictor response similar to what is observed in hypertension [16,[95][96][97]. Furthermore, insulin itself, either in the context of diabetes development or via hyperinsulinemia, also exerts an effect on autonomic reflexes, such as the arterial baroreflex [98,99]. Pricher et al [100] reported that lateral ventricular insulin infusion in rats increased baroreflex control of both heart rate and lumbar sympathetic nerve activity.…”
Section: Autonomic Function: Type 2 Diabetesmentioning
confidence: 89%
“…Type 2 diabetes has been shown to significantly modulate muscle metaboreflexinduced peripheral vascular responses by way of enhancing muscle sympathetic nerve activity and the peripheral vasoconstrictor response similar to what is observed in hypertension [16,[95][96][97]. Furthermore, insulin itself, either in the context of diabetes development or via hyperinsulinemia, also exerts an effect on autonomic reflexes, such as the arterial baroreflex [98,99]. Pricher et al [100] reported that lateral ventricular insulin infusion in rats increased baroreflex control of both heart rate and lumbar sympathetic nerve activity.…”
Section: Autonomic Function: Type 2 Diabetesmentioning
confidence: 89%
“…IR primarily promotes sodium-potassium reabsorption in distal renal tubules by directly or indirectly increasing renin-angiotensin-aldosterone system activity, leading to increased reabsorption of sodium, potassium, and water in renal tubules and resulting in increased blood volume and cardiac output [24,25]. IR can also disrupt sympathetic nervous system function, increase peripheral and renal vascular resistance, impair endothelial function, cause lipid disorders and atherosclerosis; all of which are critical factors influencing RH [26,27]. Existing clinical studies have also found that IR is an independent risk factor for autonomic imbalance based on 6-month follow-up observations [28].…”
Section: Discussionmentioning
confidence: 99%
“…Ensemble-R (Elucimed Ltd., Auckland, NZ, USA) provided systematic and monotonic three-beat increases or decreases in systolic BP and R-R intervals during controlled respiration [ 19 ]. The values were then paired as xy-coordinates to create a regression curve fitted to the BP and R-R signals [ 20 ]. We averaged slopes with correlation values of at least 0.8 for 300 s, which provided the upward sequences (BRS-up), downward sequences (BRS-down), and the average of the protocol (BRS-pooled) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%